MENINGKATKAN KEMAMPUAN BERPIKIR LOGIS PADA ANAK USIA DINI DENGAN MENGGUNAKAN MEDIA PUZZLE ANGKA - Khoirussifa Sholihah (CERIA (Cerdas Energik Responsif Inovatif Adaptif), 2018)
In the context of logical thinking the child will know about classifying objects based on function, shape or color or size, recognize patterns of ab-ab / abc-abc and repeat them. Increasing the ability to think logically with the puzzle media mental children will also be accustomed to being calm, diligent and patient in getting things done. So this research focuses on the implementation of the use of puzzle media in learning logical thinking in RA Nurul Yusro with the research title "Improving the ability of logical thinking in early childhood by using number puzzle media". This study aims at naturalist intelligence and logical thinking skills through puzzle media in group A aged 4-5 years. The use of instruments in this study was in the form of an observation sheet, in the form of a checklist of developmental achievement scales compiled based on a numerical scale assessment of 1-4. While the method used is a quasi-experimental method. The study sample was 10 children aged 4-5 years in group A RA Nurul Yusro. The results showed that the ability to think logically children aged 4-5 years in group A RA Nurul Yusro reached 35% of the minimum percentage of 65%. This shows that the ability to think logically children aged 4-5 years in group A RA Nurul Yusro is still low.